Second National Development Plan 1970-74 - The Government Printer; The Government Printer, Lagos (The Government Printer, Lagos : Lagos, Nigeria)
This publication relates to the First comprehensive progress report on the plan. It covers the first year and the first half of the second year 1971-72
MF21/01/2019
Ref
Keywords: Economic policy; Economic planning; Nigeria